2012
DOI: 10.5897/ajbm12.953
|View full text |Cite
|
Sign up to set email alerts
|

Customer relationship satisfaction and revenge behaviors: Examining the effects of power

Abstract: A customer's revenge can significantly impact a company's reputation. After a service failure, a desire for revenge is created and customers can decide to either commit direct or indirect revenge. With direct revenge, customers have a direct altercation with the company's staff and albeit negative, it allows companies the opportunity for service recovery. Indirect revenge, on the other hand, is much more damaging where customers partake in negative Word Of Mouth (WOM) both online and offline. Therefore, better… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…The present study suggested that extreme negative emotions, when evoked by undesirable brands' activities can motivate consumers to show stronger negative responses i.e., brand revenge. Such consumer revenge behavior could damage brand's reputation and consequently deter future customers (Mdakane et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The present study suggested that extreme negative emotions, when evoked by undesirable brands' activities can motivate consumers to show stronger negative responses i.e., brand revenge. Such consumer revenge behavior could damage brand's reputation and consequently deter future customers (Mdakane et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The third variable of this study is revenge, Aquino et al (2006), states that revenge is any action taken against the party that has caused any harm. Simphiwe et al (2012) suggest that any service failure can result in indirect or direct revenge by the consumers. But this study identifies that revenge cannot be triggered by anger and regret.…”
Section: Discussionmentioning
confidence: 99%
“…Online food delivery services have faced challenges regarding price, quality and advertisements, these problems can create issues related to customers' trust and online applications' credibility (Ho, 2018). According to Simphiwe, Anne, Trilby, & Elsamari (2012), service failures can result in generating a desire for direct and indirect revenge in the customers. Customer's reactions towards service failures can have positive and negative impact.…”
Section: Introductionmentioning
confidence: 99%